Reformulating mosque management strategies for optimizing assets and Islamic philanthropic funds through an analytic network process approach - Prasetyo, Iin; Siregar, Saparuddin; Nasution, Yenni Samri Juliati (Journal of Islamic Economics Lariba, 2026)
IntroductionMosques have historically functioned not only as places of worship but also as centers of education, social welfare, and economic development. Despite the large number of mosques and the substantial potential of Islamic philanthropic funds, many mosque institutions have not yet optimized their assets and financial resources to enhance community welfare. This condition has created a gap between the ideal role of mosques and their actual contribution to socioeconomic development, particularly in North Sumatra, Indonesia.ObjectivesThis study aims to formulate priority problems, solutions, and strategic directions for optimizing mosque assets and Islamic philanthropic funds through a mosque management framework grounded in maqashid al-sharia and the Capability Approach. The study seeks to identify strategic priorities that can strengthen the role of mosques as sustainable centers of community empowerment and welfare enhancement.MethodThis study employed a qualitative research design supported by the Analytic Network Process. Data were collected through in-depth interviews and pairwise-comparison questionnaires administered to nine informants consisting of academics, regulators, and mosque practitioners. The analytical framework integrated the dimensions of hifz al-din, hifz al-nafs, hifz al-‘aql, hifz al-mal, and hifz al-nasl to evaluate problems, solutions, and strategic priorities related to mosque asset management and Islamic philanthropy. The resulting network model was processed using the Super Decisions software to determine priority rankings and levels of expert consensus.ResultsThe findings reveal that the main challenges in optimizing mosque assets and philanthropic funds are associated with weaknesses in mosque management, limited literacy and managerial capacity, underutilized assets, insufficient youth engagement, and inadequate integration of social and economic programs. The highest-priority solutions include strengthening the quality of mosque administrators, enhancing educational and literacy programs, improving productive asset management, expanding social services, and promoting youth participation. Strategic priorities consist of strengthening the quality and quantity of mosque administrators, developing institutional partnerships, improving capital and audit mechanisms, intensifying mosque literacy, building integrated mosque ecosystems, and establishing sustainable mosque business models. Expert agreement regarding problem and solution priorities was very high, while strategic priorities achieved a high level of consensus.ImplicationsThe findings indicate that effective mosque transformation requires an integrated approach combining governance reform, human capital development, productive asset utilization, institutional collaboration, and sustainable economic initiatives. Strengthening these dimensions can enhance the contribution of mosques to community welfare and sustainable development.Originality/NoveltyThis study contributes to the literature by integrating maqashid al-sharia, the Capability Approach, and the Analytic Network Process into a unified strategic framework for mosque management. It offers a multidimensional model for prioritizing problems, solutions, and strategies related to mosque asset optimization and Islamic philanthropy, thereby extending existing research on mosque governance and community empowerment.